Differential Elevation of Inflammation and CD4+ T Cell Activation in Kenyan Female Sex Workers and Non-Sex Workers Using Depot-Medroxyprogesterone Acetate - Omollo, Kenneth; Lajoie, Julie; Oyugi, Julius; Wessels, Jocelyn M.; Mwaengo, Dufton; Kimani, Joshua; Kaushic, Charu; Fowke, Keith R. (Frontiers in Immunology, 2021)
Background: Depot Medroxyprogesterone (DMPA) is one of the most widely used contraceptives in Sub-Saharan Africa where HIV incidence is high. We explored the effect of DMPA on the activation of HIV cellular targets and inflammation as a possible mechanism of increased HIV risk with DMPA use. Since sex work is known to affect the immune system, this study aimed to understand the effect of DMPA on the immune system among sex workers and non-sex worker women. Methods: Twenty-seven DMPA-using HIV seronegative female sex workers (FSW) and 30 DMPA-using HIV seronegative non-sex worker (SW) women were enrolled in the study. Twenty-four FSWs and 30 non-sex workers who were not using any hormonal contraception (no HC) were recruited as controls. Blood and cervico-vaginal samples were collected from all participants and assayed for T cell activation and proinflammatory cytokines. Results: Among no HC users, sex workers had lower expression of CD38 and CD69 on blood-derived CD4+ T cells along with lower CD4+CCR5+ cells frequency in the endocervix. Plasma MCP-1, TNFα and IL-17 also had reduced expression in FSW not using HC. Non-sex workers using DMPA had elevated proportions of blood-derived CD4+CD38+, CD4+CD69+ and CD4+HLA-DR+ T cells relative to non-sex workers who were not taking any HC. DMPA-using non-sex workers also had an increased level of plasma interferon gamma (IFN-), monokine induced by interferon- (MIG) and sCD40L, alongside higher proportion of CD4+CD38+ and CD4+CD69+ T cells at the cervix compared to non-sex workers no-HC controls., Finally, non-sex workers and FSWs using DMPA had similar levels of genital and peripheral CD4+ T cell activation and inflammation. Conclusion: DMPA increased inflammation and expression of activation markers on potential HIV target cells in non-sex workers. These data show that DMPA is a strong immune modulator and its use counteracts the decreased immune activation associated with sex work. These findings suggest that inflammation and increased HIV target cells in blood and at the genital tract may be mechanisms by which DMPA increases susceptibility to HIV.